Smart Cleaning Robot for COVID – 19 Isolation Wards - Abhay A. Deshpande (International Journal of Advanced Science and Technology, 2020)
This paper deals with a smart vehicle which automatically cleans a COVID-19 Isolation ward by moving in the entire space and cleans the dust present in the ward. The sequence of the events in the cleaning procedure has a vacuum suction pump in order to suck dust from the floor of the particular terrain, and sprinkle water cum detergent on the floor which is already stored in the reservoir mounted on the system. Robotic system is monitored by microcontroller. Wiping system installed has a wiping material attached to it in order to wipe the wet floor by the sprinkling system. The ward is also monitored by series of cameras which takes pictures of the ward after specified intervals. Then it compares the pictures of the ward before and after the presence of dust. By using this comparison data, it determines the dust area and then sends the control signal to the smart cleaning robot to the specified direction to clean the ward.